TINJAUAN KRITIS MENGENAI PEMBELAJARAN SEJARAH - Tanto Sukardi (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2011)
In the fact, historical learning, as an element of social studies, and as a science in Indonesia, have no capable to give skill for students. Skill can be practiced in the day living. Many teacher of history are in the phase that themselves only as giver of learning matter, and as a person shall develop curriculum on their classroom. They often are not sensitive about development that be happened in the around society. As a consequence, historical learning matter that be teached by the teachers are quit of real situation of social environment from their students. In a general way, historial learning in many stage of education in Indonesia predominantly be executed on transfer of knowledge from teacher to student. Key words: historical learning, critical review.